Medieval Karaite Exegesis as Evidenced in Selected Examples from Yefet Ben Eli’s Commentary on the Book of Hosea - Stefański, Jacek (Collectanea Theologica, 2021)
For many years, Karaite exegesis was relatively unknown to numerous Biblical scholars. This situation has been changing with an increasing access to source materials. As a result, more and more Karaite exegetical treasures representing the trends of Karaite Judaism have come to the fore. Among them, there is the Commentary on the Book of Hosea by Yefet ben Eli, one of the most significant representatives of Karaism in the tenth century. Yefet ben Eli exhibits a remarkable knowledge of Hebrew etymology, which enables him to provide unique answers to the interpretative problems in the Masoretic Text. His apologetic concern for prospective Muslim readers of his commentary is also noteworthy. Although, in general, Karaism sought to concentrate on the literal sense of the Scripture, Yefet ben Eli does not shy away from recourses to rabbinic oral tradition. Nevertheless, his exegetical contribution remains unique, as clearly demonstrated by the selected examples from his Commentary.